Fabrication of oriented crystals as force measurement tips via focused ion beam and microlithography methods. (9th November 2017) - Wu, Zhigang; Chun, Jaehun; Chatterjee, Sayandev; Li, Dongsheng
Abstract : Detailed knowledge of the forces between nanocrystals is very crucial for understanding many generic (eg, random aggregation/assembly and rheology) and specific (eg, oriented attachment) phenomena at macroscopic length scales, especially considering the additional complexities involved in nanocrystals such as crystal orientation and corresponding orientation‐dependent physicochemical properties. Because there are a limited number of methods to directly measure the forces, little is known about the forces that drive the various emergent phenomena. Here, we report on two methods of preparing crystals as force measurement tips used in an atomic force microscope: the focused ion beam method and microlithography method. The desired crystals are fabricated using these two methods and are fixed to the atomic force microscope probe using platinum deposition, ultraviolet epoxy, or resin, which allows for the orientation‐dependent force measurements. These two methods can be used to attach virtually any solid particles (from the size of a few hundreds of nanometers to millimeters). We demonstrate the force measurements between aqueous media under different conditions such as pH.